Pengembangan Sekolah Inklusi dan Pengaruhnya terhadap Strategi Asesmen Anak Difabel di Safa Islamic Preschool Yogyakarta - Zahroh, Shofiyatuz (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
The purpose of this study is to look at the implementation of the curriculum of children withspecial needs, strategies for assessing children with special needs, methods or strategies learning of children with special needs, and the concept of inclusive education. This research was conducted at Safa Islamic Preschool Yogyakarta, 2019 which developed the curriculum 2013 and combined it with a Montessori curriculum that breathed in Islam. The method research used was qualitative with a case study approach. The results of this study are,Safa Islamic Preschool really maintains the excitement of the education system inclusive, bymaking careful planning of the learning process and the assessment of children with specialneeds. Conclusion children with special needs are able to develop their potential well in accordance with the obstacles they have, shadow teacher is able to guide children in developing their potential, the environment is able to create situations that are very supportive of children's development, assessment is carried out in accordance with rocedures with special needs